Enhancing Light Extraction Efficiency in Micro-LEDs via Metal Photonic Crystals in the Passivation Layer and Air Photonic Crystals on the n-GaN Side - Zhaoyong Liu; Gaoyu Dai; Kailin Ren; Luqiao Yin; Jianhua Zhang (IEEE Photonics Journal)
Photonic crystals (PhCs), as a type of metamaterial, have attracted significant attention due to their ability to control light propagation to enhance the light extraction efficiency (LEE) of Micro-LEDs. However, the current advancements in improving the LEE of Micro-LED with PhCs are far from 100%, and the manufacturing process for the designed optical structures is overly complex. In this work, an optical structure design requiring a simpler manufacturing process, involving metal PhCs in the passivation and air PhCs on the n-GaN side, is proposed and investigated for application in flip-chip Micro-LEDs to enhance LEE. The influence of parameters related to PhCs on LEE is investigated and analyzed using finite difference time domain simulations. Enhanced LEE is observed through the optimization of parameters such as the shape, period, height, and duty cycle of the PhCs. Under the conditions of an Ag reflector with conical Ag PhCs in the passivation layer and air conical photonic crystals on the n-GaN side, a high LEE of 81.5% is achieved, representing a 2.63-fold increase compared to the LEE of flip-chip Micro-LEDs with vertical sidewalls and Al reflector.